Successful treatment of syphilitic uveitis in HIV-positive patients - Nurfahzura MJ (Dove Medical Press, 2013)
Mohd-Jamil Nurfahzura,1–3 Hashim Hanizasurana,1 Embong Zunaina,2,3 Hussein Adil2,3 1Department of Ophthalmology, Hospital Selayang, Lebuhraya Selayang-Kepong, Selangor, Malaysia; 2Department of Ophthalmology, School of Medical Sciences, Universiti Sains Malaysia, Kelantan, Malaysia; 3Hospital Universiti Sains Malaysia, Jalan Raja Perempuan Zainab II, Kelantan, Malaysia Abstract: We report successful treatment of syphilitic uveitis in a case series of three Human immunodeficiency virus (HIV)-positive patients at Malaysia's Selayang Hospital eye clinic. All three patients with syphilitic uveitis were male, aged from 23 to 35 years old, with a history of high-risk behaviors. Of the patients, two presented with blurring of vision and only one patient presented with floaters in the affected eye. Ocular examination revealed intermediate uveitis (case 1 and case 3) and panuveitis (case 2). Each patient showed a high Venereal Disease Research Laboratory (VDRL) titer at presentation and they were also newly diagnosed as HIV positive with variable CD4 counts. All three patients responded well to a neurosyphilis regimen of intravenous penicillin G. At 3 months posttreatment, there was reduction in VDRL titer with improvement of vision in the affected eye. Diagnosis of syphilis needs to be ruled out in all cases of uveitis. All syphilitic uveitis cases should have HIV screening and vice versa, as syphilis is one of the most common infectious diseases associated with HIV-positive patients. Early detection and treatment are important for a good visual outcome. Keywords: syphilitic uveitis, penicillin, neurosyphilis, HIV-positive patient